Lymphocyte Changes in Severe COVID-19: Delayed Over-Activation of STING? - Berthelot, Jean-Marie; Lioté, Frédéric; Maugars, Yves; Sibilia, Jean (Frontiers in Immunology, 2020)
Abstract: Upon recognition of microbial DNA or self-DNA, the cyclic-GMP-AMP synthase (cGAS) of the host catalyzes the production of the cyclic dinucleotide cGAMP, the main activator of STING (stimulator of interferon genes, leading to interferon synthesis through the STING-TBK1-IRF3 pathway). STING indirectly controls enveloped RNA viruses, including coronaviruses, but excessive activation might be detrimental (STING is less efficient in bats which withstand SARS-CoV viruses). Indeed, STING is also a hub for activation of NFB and autophagy. Induction of pyroptosis also occurs downstream of STING, and increases the risk of vasculopathy. The present review details the striking similarities between T and B cell responses in severe COVID-19 and both animal or human models of STING gain of function (SAVI syndromes: STING-associated vasculopathy with onset in infancy). Those similarities may be further clues for a delayed activation of STING in severe COVID-19 patients. This should occur mostly in aged and/or obese patients, conditions which already enhance activation of STING. In early stages, Th2 differentiation are noticed in both severe COVID-19 and SAVI syndromes; then, CD4+ and CD8+ T cells functional exhaustion/senescent patterns due to TCR hyper-responsiveness are observed. T cell delayed over-responses can contribute to pneumonitis and delayed cytokine secretion with over-production of IL-6. Last, STING over-activation induces progressive CD4+ and CD8+ T lymphopenia in SAVI syndromes, which parallels what is observed in severe COVID-19. ACE2, the main receptor of SARS-CoV-2, is rarely expressed in immune cells, and it has not been yet proven that some human lymphocytes could be infected by SARS-CoV-2 through CD147 or CD26. However, STING, expressed in humans T cells, might be triggered following excessive transfer of cGAMP from infected antigen presenting cells into activated CD4+ and CD8+ T cells lymphocytes. Indeed, those lymphocytes highly express the cGAMP importer SLC19A1. Whereas STING is not expressed in human B cells, B cells counts are much less affected, either in COVID-19 or SAVI syndromes. The recognition of delayed STING over-activation in severe COVID-19 patients could prompt to target STING with specific small molecules inhibitors already designed, although Vitamine-D and aspirin should also prevent STING overactivation